Daytime naps and depression risk: A meta-analysis of observational studies - Li, Liqing; Zhang, Qi; Zhu, Liyong; Zeng, Guohua; Huang, Hongwei; Zhuge, Jian; Kuang, Xiaorui; Yang, Sule; Yang, Di; Chen, Zhensheng; Gan, Yong; Lu, Zuxun; et al. (Frontiers in Psychology, 2022)
Abstract Background: Relationship between daytime napping and the risk of depression remains debatable. Thus, a meta-analysis in this study was conducted to evaluate the relationship between daytime napping and the depression risk. Methods: PubMed, Embase, Web of Science and China National Knowledge Infrastructure databases were searched through up to February 2022, and the reference lists of the included studies were also retrieved. A random-effects model was used to estimate the combined effect size. Results: Nine studies with 649,111 participants were included in the final analysis. The pooled odd ratio (OR) was 1.15 (95% confidence interval: 1.01-1.31) with a significant heterogeneity (I2=91.3%, P for heterogeneity < 0.001), and the results demonstrated an increasing risk of depression were observed among daytime nappers. Visual inspection of funnel plot, Egger’s and Begg’s tests identified no obvious evidence of publication bias. Conclusion: This meta-analysis indicates that daytime nap plays a predictor for depressive symptom. These findings might obtain important implications for depression prevention.